An atypical presentation of Ormond's disease - João Carvão; Carlota Vida; Luís Resende; Francisca Silva; Gil Silva (Publicações Ciência e Vida, 2021)
Retroperitoneal fibrosis is a rare condition defined by an overproduction of fibro-inflammatory tissue in the retroperitoneum, usually involving the abdominal aorta, but also managing to invade adjacent structures. We report a case of a 47-year-old female patient with an atypical radiological presentation of retroperitoneal fibrosis, involving predominantly the right kidney. Ultimately, the diagnosis was performed by an immunohistochemical study that identified IgG4+ plasmocytes after kidney nephrectomy, also known as Ormond's disease. There are no universal guidelines for the treatment of retroperitoneal fibrosis, due to its rarity and lack of randomized controlled trials comparing different therapeutic strategies.